Studi Perbandingan: Dampak Pengungkapan CSR terhadap Nilai Perusahaan pada Sektor Energi dan Sektor Kesehatan di BEI - Pandiany, Nancy Bora; Puspitasari , Ayu; Indah, Djunita Permata (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study is to compare the impact of CSR disclosure on company value in the energy sector and the health sector listed on the IDX during the period 2020-2022. The author uses a quantitative approach by utilizing secondary data from annual reports and sustainability reports of companies. CSR measurement is carried out using the 2016 GRI Standards, while company value uses the Tobin's Q proxy. The findings of this study indicate that both sectors disclose that CSR has a significant impact, although the impact is greater in the energy sector than in the health sector. The results show that sector characteristics affect how effectively CSR is implemented to increase company value. It is hoped that this study will add to the literature on this issue and also offer practical suggestions on how companies can create relevant CSR strategies during economic recovery.